The United Kingdom has spoken: The receding impact of European jurisprudence on the UK interpretation of the common VAT system. (March 2020) - Zu, Yige; Krever, Richard
Post-Brexit, UK law conforming to Directives of the European Union such as the value added tax (VAT) Directive will remain in effect and UK courts will be permitted to consider decisions of the Court of Justice of the European Union (CJEU) when interpreting that law. How UK common law courts, steeped in the tradition of the doctrine of precedent, will use CJEU judgments in the post-Brexit era has been the subject of much speculation. This article considers the question in the context of a case study, looking at the application by UK courts of CJEU decisions in an important area of VAT law, the treatment of customer loyalty plan benefits. The evidence suggests that, even prior to Brexit, UK courts had started to pursue a separate path, declining to follow CJEU precedents that yielded clearly inappropriate policy outcomes. If the results of the case study are replicated more widely in UK rulings, it can be expected that the influence of CJEU judgments may taper off where formalistic and literalist CJEU interpretations have led to outcomes inconsistent with the recognized policy intent of UK law.